Medical-Grade Honey Outperforms Conventional Treatments for Healing Cold Sores-A Clinical Study - Piyu Parth Naik; Dimitris Mossialos; Bas van Wijk; Petra Novakova; Frank A. D. T. G. Wagener; Niels A. J. Cremers (MDPI AG, 2021)
Cold sores are nasolabial blisters caused by herpes simplex virus (HSV) infections. Novel therapies demonstrating simultaneously antiviral activity and improved wound healing are warranted. The aim of this study was to investigate the efficacy of medical-grade honey (MGH) for treating HSV-induced cold sores. A crossover trial was performed in patients with recurrent cold sores (n = 29). The majority (65.6%) of these patients experience four or more episodes per year, thus forming a valid self-control group. In this study, patients applied an MGH-based formulation (L-Mesitran Soft) on their cold sore at the onset of symptoms (62.1%) or appearing of blister (37.9%) and compared it to their conventional treatments. After complete healing, patients filled in a questionnaire evaluating healing, pain, and itching. The average absolute healing time was 72.4% slower with conventional treatment (10.0 days) compared to MGH (5.8 days). After MGH treatment, 86.2% of all patients experienced faster objective healing (6.9% similar and 6.9% slower) and the subjective healing score was higher in 79.3% of the patients (20.7% similar). If the patients normally experience pain and itching during their cold sores, these levels were lower with MGH therapy compared to conventional treatment in 72.7% and 71.4% of the patients, respectively. Moreover, 100% of the patients prefer MGH treatment over conventional treatment and will use it again on future cold sores. MGH is a promising alternative treatment for cold sores, likely by combining both increased antiviral and wound healing activities while alleviating pain and itching.